Analisis Kinerja Keuangan Pada PT.Federal International Finance (FIF) Cabang Barus - Ruqayyah Hafizah Sigalingging; Yenni Sofiana Tambunan; Kaharudddin Simamora (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the financial performance of PT. Fedderal International Finance (FIF) Barus Branch in terms of liquidity, solvency, activity and profitability from 2017 to 2021. The source of data in this study is secondary data where data collection is obtained through literature studies such as through books, literature, reports – reports related to the object of research. The analysis technique used is the calculation of financial ratio analysis. Research conducted at PT. Federal International Finance (FIF) Barus Branch in April 2022 . Based on the results of data analysis and discussion, it can be seen that the financial performance of PT. Federal International Finance (FIF) Barus Branch during 2017 to 2021 is in a liquid state, but there is a risk in 2020 due to the impact of covid-19, the activity is bad but increases from the previous year and still makes a profit. So it is said that PT. Federal International is doing well.